Multicriteria Risk Ranking of Zoonotic Diseases in a Developing Country: A Case Study of Zambia - Wezi, Kachinda; Brian, Chalilunda; Mataa, Liywalii; Midzi, Queen Suzan; Chisanga, Kelly; Banda, Humphrey; Zulu, Mbawe; Mwanza, Christopher K.; Ngoma, Masuzyo; Sampa, Leonard Malama; Chazya, Ricky; Mukumbwali, Milner (Journal for Research in Applied Sciences and Biotechnology, 2023)
The integration of a multicriteria decision analysis approach, including techniques such as the Analytic Hierarchy Process (AHP) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), has yielded valuable insights in the realm of zoonotic disease risk assessment. This analytical framework draws from the OIE-supported manual, utilizing impact assessments, transmission pathways, and categorizations as provided by the OIE itself. Moreover, the consideration of specific zoonotic disease scenarios tailored to individual countries enhances the contextual relevance of the analysis. Through this approach, the ranking of zoonotic diseases is systematically established, offering a comprehensive evaluation of their potential impacts and risks. This methodology encompasses pivotal criteria, including prevalence, economic impact, health impact, transmission pathways, and healthcare capacity, collectively offering a holistic perspective that mirrors the intricate nature of zoonotic diseases. The resultant rankings, derived from both ECDC and OIE data, illuminate diseases that harbor significant threats to both human and animal populations. This ranking fosters the identification of diseases with potential for rapid spread and substantial impact, guiding resource allocation towards prevention, control, and mitigation strategies. The alignment between ECDC and OIE rankings underscores the robustness of the applied methodology, with Plague and Zoonotic TB consistently emerging as high-ranking diseases, reinforcing their acknowledged significance. A consolidated ranking, amalgamating data from both sources, provides an insightful overview of potential risks linked to various zoonotic diseases. Plague, Zoonotic TB, Brucellosis, Trypanosomiasis, and Rabies consistently occupy top positions, presenting a valuable instrument for policymakers, public health officials, and stakeholders in prioritizing resource allocation and intervention strategies. The implementation of a multicriteria decision analysis approach, integrating AHP and TOPSIS methodologies, underpins the generation of informed rankings for Zambian zoonotic diseases. The intricate interplay of criteria like prevalence, economic impact, health impact, transmission pathways, and healthcare capacity forms a comprehensive framework for evaluating the potential risks of diverse diseases. The ensuing ranking, led by Plague and succeeded by Anthrax, Rabies, and others, mirrors their collective risk scores calculated via the adopted methodology. This approach empowers strategic decision-making by pinpointing diseases with heightened potential for adverse impacts on both human and animal populations. The rankings serve as invaluable aids in directing resources, devising strategic interventions, and formulating targeted measures for prevention and control. However, acknowledgment of the dynamic disease landscape and the imperative of adaptive strategies underscores the ongoing importance of monitoring and managing zoonotic diseases effectively in Zambia. By amalgamating data from authoritative sources and embracing a systematic, evidence-based approach, this study accentuates the necessity of addressing zoonotic diseases with a holistic lens, fostering proactive perspectives that augment public health and avert future outbreaks.